Prevention of thalidomide- and lenalidomide-associated thrombosis in myeloma - Palumbo, A.; Rajkumar, S.V.; Dimopoulos, M.A.; Richardson, P.G.; San Miguel, J.; Barlogie, B.; Harousseau, J.; Zonder, J.A.; Cavo, M.; Zangari, M.; Attal, M.; Belch, A.; et al. (Leukemia, 2008)
The incidence of venous thromboembolism (VTE) is more than 1‰ annually in the general population and increases further in cancer patients. The risk of VTE is higher in multiple myeloma (MM) patients who receive thalidomide or lenalidomide, especially in combination with dexamethasone or chemotherapy. Various VTE prophylaxis strategies, such as low-molecular-weight heparin (LMWH), warfarin or aspirin, have been investigated in small, uncontrolled clinical studies. This manuscript summarizes the available evidence and recommends a prophylaxis strategy according to a risk-assessment model. Individual risk factors for thrombosis associated with thalidomide/lenalidomide-based therapy include age, history of VTE, central venous catheter, comorbidities (infections, diabetes, cardiac disease), immobilization, surgery and inherited thrombophilia. Myeloma-related risk factors include diagnosis and hyperviscosity. VTE is very high in patients who receive high-dose dexamethasone, doxorubicin or multiagent chemotherapy in combination with thalidomide or lenalidomide, but not with bortezomib. The panel recommends aspirin for patients with ≤1 risk factor for VTE. LMWH (equivalent to enoxaparin 40mg per day) is recommended for those with two or more individual/myeloma-related risk factors. LMWH is also recommended for all patients receiving concurrent high-dose dexamethasone or doxorubicin. Full-dose warfarin targeting a therapeutic INR of 2-3 is an alternative to LMWH, although there are limited data in the literature with this strategy. In the absence of clear data from randomized studies as a foundation for recommendations, many of the following proposed strategies are the results of common sense or derive from the extrapolation of data from many studies not specifically designed to answer these questions. Further investigation is needed to define the best VTE prophylaxis.